Pengaruh Latihan Propioseptif Terhadap Keseimbangan Lansia Di Bina Asih Rw 7 Kelurahan Jagir Kecamatan Wonokromo Kota Surabaya - Besty Mergyaning Utami; Yohanes Deo Fau; Amin Zakaria; Fransisca Xaveria Hargiani (Jurnal Keperawatan Muhammadiyah, 2023)
Propioceptive is the ability of the body to transfer a sense of position, break information and respond intentionally or unintentionally to lead to the right choice of action. The aging process in humans accompanied by a decrease in the ability of organs will cause disturbances in the motor body (motion function) and sensory (taste), cognitive (intelligence), memory, decreased propioceptive ability, as well as impaired balance and coordination. Propioceptive exercise is an exercise formed to increase propioceptive. If the exercise is carried out regularly, then it will be useful to restore and improve the balance.